Implementation of Green Entrepreneurship Orientation and Green Innovation to Achieve Business Performance - Mesti Septiani; Arif Nugroho; Widya Lelisa Army (ITQAN: Journal of Islamic Economics, Management, and Finance, 2026)
Green entrepreneurship, which emphasizes environmental and social sustainability, is growing in various countries, including developing countries. According to the Global Entrepreneurship Monitor (GEM, 2020), approximately 25% of new businesses in developing countries are oriented towards green innovation. This reflects the growing awareness of business actors regarding the importance of sustainability in business models. Despite this positive trend, the integration of green entrepreneurship into business practices still faces various challenges. This study aims to examine the effect of Green Entrepreneurship Orientation and Green Innovation on Business Performance. This study uses a quantitative method with a descriptive and analytical design. This design was chosen to describe the actual conditions of green entrepreneurship implementation, the level of green innovation, and its impact on business performance. This approach allows for analysis of relationships between variables through systematic data collection and statistical testing of formulated hypotheses. The results of this study indicate that the implementation of green entrepreneurship orientation and green innovation has a positive and significant impact on the business performance of MSMEs in Karawang Regency. These findings provide the basis for formulating policies that encourage the development of environmentally based entrepreneurship while supporting the achievement of sustainable development goals (SDGs) at the local level. This finding also provides important implications from the perspective of Islamic economics, particularly in realizing the maqashid of sharia through sustainable business practices.